Cell specific perfusion rates drive growth dynamics and metabolism in CHO N-1 perfusion processes independent of perfusion rate control method - Julia Walther; Tiago Ribeiro da Costa; Lydia Winkler; Jochen Schaub; Tobias Habicher (Frontiers in Bioengineering and Biotechnology)
The production of monoclonal antibodies (mAbs) using Chinese Hamster Ovary (CHO) cell host systems often faces challenges in terms of manufacturing costs and efficiency. To address these challenges, process intensification with high seeding density production processes applying N-1 perfusion is utilized. This study delves into the impact of cell specific perfusion rate (CSPR) and the total exchanged medium in relation to the reactor working volume (iVVD) on cell growth dynamics and metabolic stability in N-1 perfusion cultivations. The effect of varying the perfusion rate increase (PRI) while keeping the amount of exchanged medium constant is investigated, revealing a positive correlation between iVVD and overall cell growth. However, this effect plateaus at higher values, indicating diminishing returns on cell growth with increased medium use. We found that CSPR directly influences the specific metabolic rates of several metabolites and amino acids, accelerating overall metabolism without necessarily affecting growth. Interestingly, the specific metabolic rates are driven by the CSPR after a metabolic adaptation until day 2.5. Besides adjusting perfusion rates every 24 h, the potential benefits of real-time CSPR control using a capacitance probe are explored. While real-time control offers more precise regulation of the perfusion rate, growth and metabolic behavior is comparable to predefined rates within the tested range. This study demonstrates that optimization of factors such as CSPR, iVVD, and PRI can lead to improved cell growth and viability with the potential to decrease media expenditure, thereby reducing manufacturing costs for the production of mAbs using CHO cell host systems.